State estimator condition number analysis. - Ebrahimian, R. (IEEE Transactions on power systems)
This paper develops formulas for the condition number of the state estimation problem as a function of the different types and number of measurements. We present empirical results using the IEEE RTS-96 and IEEE 118 bus systems that validate the formulas